Resolving the Taxonomic Status of Potential Biocontrol Agents Belonging to the Neglected Genus Lipolexis Förster (Hymenoptera, Braconidae, Aphidiinae) with Descriptions of Six New Species † - Kocić, Korana (Insects, 2020)
SIMPLE SUMMARY: Lipolexis is small but widely distributed genus across Europe and Asia. Nevertheless, its taxonomic distinctiveness was subsequently questioned by some authors who considered it as a synonym of the genus Diaeretus. Although Lipolexis is widely distributed and one species (Lipolexis oregmae Gahan) is an important biological control agent, the last taxonomic study on it was conducted more than 50 years ago. Our study employs an integrative approach (morphology and molecular analysis (COI barcode region)), to examine Lipolexis specimens that were sampled worldwide, including specimens from BOLD database. It led to the description of six new species. Each of the new species possesses clear morphological characters that distinguishes it from its congeners. Our findings suggest that two groups can be differentiated within the genus—oregmae and gracilis. Furthermore, we present a key for the identification to all known Lipolexis species of the world. ABSTRACT: Lipolexis is a small genus in the subfamily Aphidiinae represented by one species in Europe (Lipolexis gracilis Förster) and by four in Asia (Lipolexis wuyiensis Chen, L. oregmae Gahan, L. myzakkaiae Pramanik and Raychaudhuri and L. pseudoscutellaris Pramanik and Raychaudhuri). Although L. oregmae is employed in biological control programs against pest aphids, the last morphological study on the genus was completed over 50 years ago. This study employs an integrative approach (morphology and molecular analysis (COI barcode region)), to examine Lipolexis specimens that were sampled worldwide, including specimens from BOLD database. These results establish that two currently recognized species of Lipolexis (L. gracilis, L. oregmae) are actually a species complex and also reveal phylogenetic relationships within the genus. Six new species are described and a global key for the identification of Lipolexis species is provided.